Drug-coated balloon: an effective alternative to stent strategy in small-vessel coronary artery disease—a meta-analysis - Felbel, Dominik; Bozic, Filip; Mayer, Benjamin; Krohn-Grimberghe, Marvin; Paukovitsch, Michael; d’Almeida, Sascha; Mörike, Johannes; Gonska, Birgid; Imhof, Armin; Buckert, Dominik; Rottbauer, Wolfgang; Markovic, Sinisa; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Small vessel coronary artery disease (CAD) is frequently observed in coronary angiography and linked to a higher risk of lesion failure and restenosis.Currently, treatment of small vessels is not standardized while having drug eluting stents (DES) or drug coating balloons (DCB) as possible stragies. We aimed to conduct a meta-analytic approach to assess the effectiveness of treatment strategies and outcomes for small vessel CAD.Comprehensive literature search was conducted using Pubmed, EMBASE, MEDLINE and Cochrane library databases to identify studies reporting treatment strategies of small vessel CAD with a reference diameter ≤3,0 mm. Target-lesion revascularization (TLR), target-lesion thrombosis (TLT), all-cause death, myocardial infarction (MI) and major cardiac events (MACE) were defined as clinical outcomes.Outcomes from single-arm and randomized studies based on measures by means of their corresponding 95% confidence intervals (CI) were compared using a metaanalytic approach. Statistical significance was assumed if CIs did not overlap.Results 37 eligible studies with a total of 31.835 patients with small vessel CAD were included in the present analysis. Among those, 28.147 patients were treated with DES (24 studies) and 3.299 patients with DCB (17 studies). Common baseline characteristics were equally distributed in the different studies. TLR rate was 4% in both treatment strategies (0.04; 95%-CI 0.